Konstruksi Berita “Kepulangan WNI Dari Malaysia Akibat Pandemi Covid-19“ Pada Media Online Tribun Batam.Id dan Haluan Kepri.Id - kasirul fadli (Communicology: Jurnal Ilmu Komunikasi, 2021)
ABSTRACT This study aims to determine the construction of news related to the Covid-19 pandemic on the Batam.Id Tribune Online Media and the Kepri.Id Bow. The theories used by the researcher in this study are: Mass Media and Reality Construction, News as a Result of Reality Construction, Journalists as Reality Construction Agents, and Framing Analysis Including Constructivist Paradigms, are used to describe the selection process and highlight certain aspects of reality by the media. The method used in this research is descriptive qualitative research method, which uses Framing Model Analysis from Robert N. Entman. Framing tools used in measuring this research are: Define Problems (Defining the problem), Diagnose causes (Estimating the problem or source of the problem), Make Moral Judgment (Make moral decisions) and Treatment Recommendations (Emphasize the Solution). The variables of the news are: News that discusses the return of Indonesian citizens/TKI from Malaysia, due to the impact of the Covid-19 Pandemic. Keywords: Covid-19 pandemic News; News Construction; Online Media Framing Analysis